Understanding peasant household's land transfer decision-making: A perspective of financial literacy. (August 2022) - Tan, Jing; Cai, Dongliang; Han, Kefei; Zhou, Kui
Abstract: This paper investigates the effect of peasant households' financial literacy on their land transfer, using representative survey data conducted in less-developed rural regions of China (N = 1302). The empirical results show that: (1) Financial literacy significantly influences land transfer. (2) Financing condition and risk tolerance work as mediators in this relationship. (3) Land transfer decisions of households characterized as high agricultural dependence, low income, large size of arable land ownership, and female, elder, and high education decision-makers are more sensitive to financial literacy. (4) Financial literacy has a greater impact on land inflow than outflow; advanced literacy is more beneficial for land transfer than basic literacy; and consistency in subjective and objective literacy moderates the relationship between financial literacy and land transfer. Our findings could provide some implications for stimulating the development of rural land transfer markets. Highlights: Financial literacy significantly influences land transfer in rural China. Financing condition and risk tolerance work as mediators in the relationship. The effect of financial literacy on land transfer varies by characteristics of decision-makers and household. Financial literacy has a greater impact on land inflow than outflow; advanced literacy is more useful than basic literacy. Consistency in subjective and objective literacy moderates the relationship between financial literacy and land transfer.